IMPLEMENTASI AUGMENTED REALITY PADA E-MODUL INTERAKTIF SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN PARTISIPASI DAN MOTIVASI BELAJAR MAHASISWA - Firmanilah Kamil; Nely Kurnila; Saima Putrini R Harahap (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
The development of digital technology, particularly Augmented Reality (AR), opens up opportunities for more interactive and engaging learning media innovations. This study aims to: (1) describe students’ perceptions of interactive AR-based e-modules; (2) analyze the impact of using interactive AR-based e-modules on students’ learning motivation; and (3) assess the level of student participation in learning after using interactive AR-based e-modules. The research method employs a descriptive quantitative design with 58 students as subjects. Data were collected through a Likert scale questionnaire that had been tested for validity and reliability. The results showed that the perception variable had an average score of 4.15 (scale 1–5), with 44.8% of students in the very positive category and 55.2% in the positive category. The motivation variable increased from 3.50 in the pretest to 4.36 in the posttest, with 51.7% in the very high category and 48.3% in the high category. The participation variable rose from 3.72 to 4.33, with 50% in the very high category and 50% in the high category. These findings indicate that AR-based e-modules can enhance learning interest, facilitate material comprehension, and encourage active student engagement.